BMC health services research title: the 2020 blast in the port of Beirut: can the Lebanese health system "build back better"? - Michel D. Landry; Mohamad Alameddine; Tiago S. Jesus; Saydeh Sassine; Elie Koueik; Sudha R. Raman (BMC, 2020)
Abstract The August 2020 explosion in Lebanon resulted in casualties, injuries, and a great number of internally displaced persons. The blast occurred during an economically and politically complex time in the country. Given multiple and competing post-explosion reconstruction priorities, in ths editorial we briefly examine the requirements for a build back better scenario.